Sequential innovation, patent policy, and the dynamics of the replacement effect. (25th June 2019) - Parra, Álvaro
Abstract: I study how patent policy—characterized by patent length and forward protection—affects Research and Development (R&D) dynamics, leadership persistence, and market structure. Firms' R&D investments increase as the patent's expiration date approaches. Through forward protection, followers internalize the leader's replacement effect. In protective systems, this internalization is substantial, reversing Arrow's traditional result: followers invest less than leaders at every moment of the patent's life. I study the policy that maximizes innovative activity. Overly protective policies decrease innovation pace through two mechanisms: delaying firms' investments toward the end of the patent's life and decreasing the number of firms performing R&D.